Investigation of modified bitumen binders via Fourier-transform infrared spectroscopy - I. V. Gordeeva (Тонкие химические технологии, 2020)
Objectives. This study evaluates the effect of the modification process on the group composition of bitumen and bitumen binders containing rubber powder and hybrid modifier that is based on styrene–butadiene thermoplastic elastomer and rubber crumb. The aim of the study was to determine the presence or absence of functional groups that reflect the direction of physicochemical processes during the preparation of a hybrid modifier in rotary dispersers and during the modification of bitumen binders. Methods. Rubber powder and hybrid modifier were obtained by high-temperature shear grinding using a rotary disperser. Bitumen and modified bitumen binders were investigated via Fouriertransform infrared spectroscopy. Using the method of spectral subtraction, it was determined that during the process of manufacturing modified bitumen binders, structural changes occur in both bitumen and modifiers. During this study, the extraction of modifiers (rubber powder and hybrid modifier) in toluene was performed. Results. The quantitative analysis of changes in the group composition of modifiers before and after the modification procedure was carried out. The active polymer and structural indices were determined. The general trend of the change in the active polymer and structural indices was noted for the initial spectra of the rubber powder and hybrid modifier, and their spectra were obtained after the procedure of subtraction from the spectra of bitumen binders. Conclusions. The interdiffusion of aromatic compounds between the bitumen component and modifier particles was confirmed. On the basis of the results of the extraction of modifiers in toluene, and by taking into account the infrared spectroscopy data, it was determined that during the production of hybrid modifier during the simultaneous grinding of rubber crumb and styrene– butadiene thermoplastic elastomer, there was a chemical interaction between them.